An Interdisciplinary Legal Study of the Organisation of the Courts: The Methodological Consequences of the Meeting between Legal and Management Approaches (Penelitian Hukum Interdisipliner pada Organisasi Peradilan: Pertemuan Pendekatan Hukum dan Pendekatan Manajemen Serta Konsekuensi Metodologisnya) - Rositawati, Dian (The Indonesian Journal of Socio-Legal Studies, 2022)
This article presents the relationship between legal principles and management principles in the judicial organization and how they affect the judiciary's performance. As an organization, the judiciary is bound by the rule of law principles, especially the principle of judicial independence, as stated in the constitution and laws. However, the courts as an organization are also influenced by management principles, which include viewing public organizations from efficiency, effectiveness, and service quality perspectives. This paper discusses the interaction and tension between these principles in a judicial organization and their methodological consequences. In the discussion about methodology, this paper will elaborate on the application of interdisciplinary legal research methods as a consequence of the dynamics between the two perspectives in the judicial organization. The discussion of the methodology will also cover the technical aspects of the application of research methods, so it is expected to fulfill a practical function in assisting legal researchers in applying interdisciplinary legal research.